(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article analyzes the temporal organization of the text as a key factor in the formation of the artistic structure of the work. The relevance of the research is determined by current trends in literary studies focused on the comprehensive study of text-forming categories, as well as the need for an interdisciplinary understanding of time as a structural and semantic element of a literary work. In modern cultural and educational contexts, as noted by President of Uzbekistan Shavkat Mirziyoyev, the development of spiritual and artistic values plays a central role in fostering a harmonious and socially responsible society, which makes the study of the temporal structures of the text particularly significant. The aim of the study is to identify the features of the temporal organization of a literary text and its role in the formation of the structure of the work, semantic dominants and artistic perception of the reader.